1994
DOI: 10.1128/jvi.68.5.3364-3368.1994
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid change determines persistence of a chimeric Theiler's virus

Abstract: The DA strain of Theiler's virus persists in the central nervous system of mice and causes chronic inflammation and demyelination. On the other hand, the GDVII strain causes an acute encephalitis and does not persist in surviving animals. Series of recombinants between infectious cDNA clones of the genomes of DA and GDVII viruses have been constructed. The analysis of the phenotypes of the recombinant viruses has shown that determinants of persistence and demyelination are present in the capsid proteins of DA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 30 publications
4
32
0
1
Order By: Relevance
“…Chimeric viruses between GDVII (an extremely neurovirulent variant which induces only acute encephalitis and does not persist) and DA or BeAn (which cause persistence and demyelination) strains have been constructed. The major finding of these studies is that the viral capsid plays a major role in persistence (3,178,280,454). Within the capsid, several amino acids have been identified as being involved in establishing persistent infection (178,409,426,524).…”
Section: Determinants Of Viral Persistencementioning
confidence: 99%
See 2 more Smart Citations
“…Chimeric viruses between GDVII (an extremely neurovirulent variant which induces only acute encephalitis and does not persist) and DA or BeAn (which cause persistence and demyelination) strains have been constructed. The major finding of these studies is that the viral capsid plays a major role in persistence (3,178,280,454). Within the capsid, several amino acids have been identified as being involved in establishing persistent infection (178,409,426,524).…”
Section: Determinants Of Viral Persistencementioning
confidence: 99%
“…The major finding of these studies is that the viral capsid plays a major role in persistence (3,178,280,454). Within the capsid, several amino acids have been identified as being involved in establishing persistent infection (178,409,426,524). It has been suggested that persistence depends on a conformational determinant within the capsid requiring homologous sequences in both the VP2 puff and VP1 loop, which Early acute disease Intense and multifocal mononuclear cell infiltrates in the grey matter of brain and spinal cord Attenuated grey matter disease, clinically inapparent 86,87,250,386,474 Late chronic demyelinating disease Clinically apparent at ϳ140-180 p.i.…”
Section: Determinants Of Viral Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the passaged strain affect interactions between residues at positions 62 and 160. The VP2 and VP3 proteins of Cardiovirus B species are known to form the pentamer lattice on the virion surface (33) and play critical roles in viral infection (41)(42)(43)(44). To address the structural impacts of the three mutations in the capsid proteins of the AM-5Cb strain, we constructed molecular models of the VP2 and VP3 proteins in the virion.…”
Section: Mouse-passaged Safv-3 Acquired Three Amino Acid Mutationsmentioning
confidence: 99%
“…Viral variants, even single amino acid substitutions, can exhibit remarkable differences in their expression pattern in cells and tissues of the infected host, that are associated with diverse disease phenotypes [98,210]. Similarly, genetic differences among individuals play a critical role in the outcome of a viral infection [32].…”
mentioning
confidence: 99%